Homonymy in "It Ends with Us" Novel by Colleen Hoover (e-Journal of Linguistics, 2023)
This study aims to analyze homonymy found in Colleen Hoover'snovel It Ends with Us. The method that used in this study isqualitative research, which is the writer investigate phenomena inthe natural contexts, attempting to make sense of or interpretphenomena in terms of the meanings that people assign to them. Thedata was taken from the source of data, which is from ColleenHoover's novel, It Ends with Us. The result of this study is thewriters found that there are 3 types homonyms, which is consist of 2pairs of absolute homonym, 2 pairs of homograph, and 3 pairs ofhomophone in Colleen Hoover's novel It Ends with Us, and thedominant types of homonymy in Colleen Hoover's novel "It EndsWith Us" is homograph
Keywords: Homograph; Homonym; Homonymy; Homophones; Novel